Синтез в искусстве: конфигурации на основе музыки - Мкртчан, К.А. (Культура народов Причерноморья, 2014)
В статье рассматриваются конфигурации взаимодействия музыки с другими видами
искусства. В статтi розглянутi конфiгурацїї взаємодії музики з iншими видами мистецтва. Article problematizing the notion of "synthesis of arts". The article examines form-creating potential
of music. Synthesis may be accomplished on various configurations. In artistic synthesis the role of each of the
arts involved need not be the same. One form may dominate completely. The early romantic theories as the
problem of creating synthetic works of art. The idea of synthesis of music and poetry in a new synthetic level has
been especially close to Franz Liszt. Some of his most notable contributions were the invention of the symphonic
poem. These works helped establish the genre of orchestral program music – compositions written to illustrate
an extra-musical plan derived from a play, poem, painting. On the example of Modest Mussorgsky’s "Pictures at
a exhibition" exposed prerequisites of diversity of art result in creativity of the composer, connected with his
aspiration most precisely to embody word and music synthesis reveal. The subjects of the article are specific and
limits of artistic expressiveness of music and systematization of opportunities for their diverse synthetic
relationships.